DIPLOMASI PUBLIK KOREA SELATAN DI INDONESIA : Studi Kasus Peran BTS Dalam Mendukung Diplomasi Publik Korea Selatan di Indonesia tahun 2017-2021 - Zahra Meita Anindya (2022)
After gaining great attention from a wide audience and being given the name Hallyu or Korean Wave in the late 2000s, the South Korean government began to use its popular culture industry as their public diplomacy approach. South Korea takes advantage of the development of the International system and uses its Popular Culture in building its Soft Power strategy. In this case, BTS as part of the Korean Wave itself is present in a more specific framework in Public Diplomacy activities as non-state actors who have successfully garnered global attention and become a big phenomenon in the world and have gained recognition and validation as global popular culture. This study focuses on the role of BTS in supporting South Korean public diplomacy and spreading its influence in Indonesia. The choice of BTS as the subject of this research is because BTS is one of the most successful forms of manifestation of the Korean Wave and has created a direct impact on South Korea. In analyzing, this research uses a qualitative case study method to provide descriptive answers based on the facts found. This study found that BTS as a non-state actor has succeeded in playing an active role and contributing to the achievement of the goals of South Korean Public Diplomacy in Indonesia, one of which is increasing the positive image of South Korea and economic benefits.